Pain medication use in youth athletes: A cross-sectional study of 466 youth handball players - Sari, D. M.; Rønne Pedersen, J.; Bloch Thorlund, J.; Ramer Mikkelsen, U.; Møller, M. (Translational Sports Medicine, 2021)
The aim of this study was to determine the 4-week prevalence of pain medication use in youth athletes, the type of medication used, the reasons for use, and from where the athletes obtained the medication. 466 handball players (aged 14-18) were surveyed about their pain medication use within the preceding 4 weeks. The questionnaire consisted of 3 parts: type of pain medication used (if any; non-steroidal anti-inflammatory drugs (NSAIDs), acetaminophen/paracetamol, and acetylsalicylic acid (ASA)), the reasons for use, and from where it was obtained. 190 players (41% [95% CI 36%-45%]) reported pain medication use within the last 4 weeks. Paracetamol was the most reported type (n = 157, 83% [95% CI 77%-88%]), followed by NSAIDs (n = 98, 52% [95% CI 44%-59%]); 67 reported "injury-related reasons" for their use, and most participants reported to obtain the pain medication via "from home or bought over-the-counter (OTC)" (n = 167, 88% [95% CI 82%-92%]). Pain medication use in youth handball players is common, particularly among female players, and a substantial proportion of the overall use is due to injury-related reasons. The vast majority of the players got their pain medication from home or purchased it OTC. Further research is needed to comprehend these patterns of use, including the long-term use.